Analysis of White Pepper Farming Financial Feasibility with Good Agricultural Practices (GAP) Method and Pepper Powder Business Feasibility in Bangka Belitung Islands Province: Analisis Kelayakan Finansial Usahatani Lada Putih (Muntok White Pepper) dengan Metode GAP dan Kelayakan Usaha Lada Bubuk di Provinsi Kepulauan Bangka Belitung (Journal of Integrated Agribusiness, 2019)
The Bangka Belitung Islands Province is one of the provinces that produces the largest white pepper production in Indonesia. However, white pepper exports in the Bangka Belitung Islands Province have decreased and pepper prices have also fluctuated. Therefore, it is necessary to cultivate white pepper farming using the GAP method which aims to increase productivity and product quality and create derivative products, namely powdered pepper. The purpose of this study was 1) to analyze the financial feasibility of white pepper farming in the Province of Bangka Belitung Islands by applying GAP and 2) to analyze the feasibility of the pepper powder business in the Bangka Belitung Islands Province. This research method is a case study method. Data processing and analysis uses two methods, namely quantiative and qualitative. The results showed that 1) white pepper farming in the Bangka Belitung Islands Province carried out by the Pepper Management, Development and Marketing Agency (BP3L) and the Agricultural Seed Center (BBP) using the GAP method was financially feasible to be cultivated with NPV of Rp 234,474,027 , 32, IRR of 25 percent, Net B / C of 2.8, and Payback Period of 4 years 6 months and for analysis of break-even points of white pepper is also beneficial and 2) pepper powder business in the Province of Bangka Belitung Islands conducted by CV. Indobakti is non financially and financially feasible to be cultivated with NPV of Rp. 3,620,047,323.41, IRR of 58 percent, Net B / C of 4.4, and Payback Period of 1 year 7 months and for analysis of break-even points of pepper powder is also beneficial.